Toxoplasma gondii infection induces suppression in a mouse model of allergic airway inflammation. - Ignacio M Fenoy (Public Library of Science (PLoS), 2012)
Allergic asthma is an inflammatory disorder characterized by infiltration of the airway wall with inflammatory cells driven mostly by activation of Th2-lymphocytes, eosinophils and mast cells. There is a link between increased allergy and a reduction of some infections in Western countries. Epidemiological data also show that respiratory allergy is less frequent in people exposed to orofecal and foodborne microbes such as Toxoplasma gondii. We previously showed that both acute and chronic parasite T. gondii infection substantially blocked development of airway inflammation in adult BALB/c mice. Based on the high levels of IFN-γ along with the reduction of Th2 phenotype, we hypothesized that the protective effect might be related to the strong Th1 immune response elicited against the parasite. However, other mechanisms could also be implicated. The possibility that regulatory T cells inhibit allergic diseases has received growing support from both animal and human studies. Here we investigated the cellular mechanisms involved in T. gondii induced protection against allergy. Our results show for the first time that thoracic lymph node cells from mice sensitized during chronic T. gondii infection have suppressor activity. Suppression was detected both in vitro, on allergen specific T cell proliferation and in vivo, on allergic lung inflammation after adoptive transference from infected/sensitized mice to previously sensitized animals. This ability was found to be contact-independent and correlated with high levels of TGF-β and CD4(+)FoxP3(+) cells.